Welded beam-to-column steel joints: Assessment of European design rules - Conde, Jorge; Freire, Fernando; Ljubinković, Filip; Vild, Martin; da Silva, Luís Simes (Elsevier, 2024)
Properly validated high-quality Finite Element (FE) models with experimental tests permit an accurate description of the load-deformation path and stress state of steel joints and are nowadays accepted as “experimental results”. Changes to the design of welded joints in Eurocode 3 are currently proposed that affect the resistance and stiffness of the components associated with the column web panel. This paper presents an assessment of the design formulations included in the current Eurocode 3, part 1–8, and its forthcoming update in terms of stiffness and moment resistance, compared against a large parametric study of strong-axis beam-column welded joints for open sections carried out using validated sophisticated FE models. The results show that both the old and new Eurocode formulations provide a large scatter and no big differences between both methods. Additionally, the presence of axial force in the column shows a clear increase in the ratio between design resistance vs numerical resistance that, particularly in the case of transversally stiffened joints, may be unconservative.

Properly validated high-quality Finite Element (FE) models with experimental tests permit an accurate description of the load-deformation path and stress state of steel joints and are nowadays accepted as “experimental results”. Changes to the design of welded joints in Eurocode 3 are currently proposed that affect the resistance and stiffness of the components associated with the column web panel. This paper presents an assessment of the design formulations included in the current Eurocode 3, part 1–8, and its forthcoming update in terms of stiffness and moment resistance, compared against a large parametric study of strong-axis beam-column welded joints for open sections carried out using validated sophisticated FE models. The results show that both the old and new Eurocode formulations provide a large scatter and no big differences between both methods. Additionally, the presence of axial force in the column shows a clear increase in the ratio between design resistance vs numerical resistance that, particularly in the case of transversally stiffened joints, may be unconservative.
Welded beam-to-column steel joints: Assessment of European design rules
Keywords: Welded steel joints; Column web in compression; Column web in tension; Column web in shear; FEM; Eurocode 3; Component method; Welded steel joints; Column web in compression; Column web in tension; Column web in shear; FEM; Eurocode 3; Component method